Using Communicative Approach in Teaching Speaking Competence of Young Learners through Home-based Learning - Maria C.R, Irene (KnE Social Sciences, 2021)
This study aims to probe into the use of communicative approach in teaching speaking competence of young learners through a Home-based Learning approach. To master a language, the learner should sharpen their speaking skills/competences. In Indonesia, English is taught as a foreign/second language to young learners. Developing speaking competence will teach young learners English beyond grammar and word function, so that they could freely express their opinions. Being able to express themselves, young learners will have good self-esteem which would, in turn, help them in learning new things and other languages. However, the COVID-19 pandemic urged teachers to alter their method of teaching speaking to young learners as they learn from home and meet their teachers online through a virtual meeting platform. This study found that the materials designed by the teacher do impact in stimulating young language learners to improve their communication skills in English. Keywords: communicative approach, speaking skill, teaching young learners